Fiscal policy and Dutch disease - Frederick van der Ploeg (Center for Economic Studies and ifo Institute (CESifo), 2011)
In this paper we revisit the Dutch disease paying particular attention to the role of specific factors of production and capital stock dynamics. The main insight is that if the natural resource rich windfall is substantial but not large enough for the country to become a rentier, capital goods must be produced at home and adjustment to natural resource windfall takes time. It takes time to build this home-grown capital. Specific factors are crucial to explain the dynamic responses of the real exchange rate, capital intensities and wages in response to a natural resource windfall. If a country is small and the windfall is large, it may be able to import capital and migrant labour in which case the Dutch disease can be avoided.
Keywords: E01; F43; O41; Q30; 330; specific factors; real exchange rate; capital stock dynamics; factor intensity; international trade; Dutch disease; permanent income; fiscal policy rules; overlapping generations; Dutch Disease; Finanzpolitik; Investitionspolitik; Faktorintensität; Mehr-Sektoren-Modell; Overlapping Generations; Theorie